Analysis Influence Expenditure Government, Inflation, Number Population and Inequality Distribution Income to Economic Growth in Indonesia 1993-2022 - Dika Saputra, Erzza; Soelistyo, Aris (Jurnal Ilmu Ekonomi JIE, 2024)
This study aims to determine the effect of the elasticity of government expenditure, inflation, population and income distribution inequality on economic growth (changes in the magnitude of GDP). The method used in this study is multiple linear regression analysis. The study results indicate that the elasticity of government expenditure and population is positive and significant. Inflation elasticity has a negative and insignificant effect on economic growth. Meanwhile, the elasticity of income distribution inequality has a positive and negligible impact on economic growth.